Internal thoracic artery: A major collateral supply in case of Leriche syndrome - Meriç, Mert; Öztaş, Didem Melis; Uğurlucan, Murat (My University, 2020)
We read with great interest the article by Bosse and colleagues,1 in which they presented a case series of cardiac surgery combined with bypass from the ascending aorta to the bilateral femoral arteries in patients with severe aorta-iliac occlusion.
Keywords: Internal Thoracic Artery; Major Collateral Supply; Leriche Syndrome